Revision of the stag beetle genus Ryssonotus MacLeay (Coleoptera: Lucanidae), with descriptions of a new genus and three new species - Reid, C. A. M.; Beatson, M. (Zootaxa, 2016)
The Australian lucanid genus Ryssonotus MacLeay, 1819 is redefined and reduced to one species: R. nebulosus (Kirby, 1819). The supposed senior synonym of this species, Lucanus foveolatus Thunberg, 1806 is a junior synonym of the North American species Lucanus capreolus (Linnaeus, 1763) (new synonym). Safrina new genus, is described for the remaining species formerly in Ryssonotus and three new species: S. dekeyzeri new species, S. grandis (Lea, 1915) new combination, S. jaedoni new species, S. jugularis (Westwood, 1863) new combination, S. laticeps (Macleay, 1885) new combination, S. moorei new species, S. parallela (Deyrolle, 1881) new combination, and S. polita (Carter, 1921) new combination. Safrina grandis is a senior synonym of S. costata (Carter, 1929) new synonym. The type species of Safrina is Rhyssonotus laticeps Macleay, 1885. All species of Safrina are described and a key is provided to the adults of Ryssonotus and Safrina. The species are confined to the ranges of eastern mainland Australia. Diagnostic descriptions of the larvae of Ryssonotus and Safrina are provided. Safrina and Ryssonotus are placed in the tribe Chiasognathini and their systematic position is discussed.